Dispensasi Perkawinan Setelah Berlakunya Undang-Undang Nomor 16 Tahun 2019 Tentang Perubahan Undang-Undang Nomor 1 Tahun 1974 - Purnomo, Fajar Galih (UM Purwokerto Press, 2024)
This research aims to find out what factors cause the increase in marriage dispensations, the judges' reasons for granting requests for marriage dispensations at the Regency Religious Courts and legal protection for minors who enter into marriages without obtaining a marriage dispensation from the court. Basically, the panel of judges looks at the situation. Applicants who apply for marriage dispensation are based on the factors of being pregnant out of wedlock, the administrative completeness factor, the factor that there is no prohibition on marriage, the principle of benefit and harm. The judge's consideration in determining the request for Marriage Dispensation refers to two sources, the first is the legal source which formulates statutory regulations between Article 7 Paragraphs (1) and (2) of Law no. 16 of 2019 concerning Marriage.